Restoring Angiogenic Balance in Diabetes: Advanced Molecular Therapeutics for Non-Healing Diabetic Wounds and Cellular Medicines for Diabetic Retinopathy - Sheets, Anthony. (2018)
Abstract: The microvascular complications of diabetes are associated with a tremendous degree of morbidity and mortality. Indeed, type I and type II diabetes are leading causes of adult-onset retinal damage and blindness, non-healing foot ulcers that may require amputation, and end-stage renal disease around the world. Intriguingly, while these debilitating conditions arise from long-standing, hyperglycemia-driven inflammation and vascular insult, diabetic microangiopathies have strikingly tissue-specific manifestations: chronic wounds in the extremities of diabetic patients are hallmarked by their impairments in vascular growth and matrix turnover after injury, whereas retinopathy is characterized by florid vascular overgrowth that has long been ascribed to the loss of microvascular pericytes from the retinal circulation. The work performed in our laboratory and center aims to further elucidate the molecular and cellular mechanisms of angiogenesis, in order to better understand the pathogenesis of these diabetes-associated vasculopathies and develop advanced molecular and cellular therapeutics for these conditions. Linked to these goals, our investigations of cell-matrix interactions in angiogenesis and wound healing have resulted in the creation of several bioactive, matrix-derived peptides that induce cellular migration, proliferation and morphogenesis necessary for tissue repair. And, at the same time, our studies of pericyte-endothelial interactions reveal that subtle alterations in pericyte chemo-mechanics - rather than their frank disappearance - may be sufficient to permit endothelial cell cycle re-entry and angiogenesis. Herein, we demonstrate that bioactive matrix- and plasma-derived peptides significantly increase re-epithelialization and angiogenesis in diabetic porcine wounds through upregulation of multiple reparative growth factors and cytokines, especially matrix metalloproteinases and inhibitors that may aid in reversing the proteolytic imbalance characteristic of chronically inflamed non-healing wounds. Additionally, we reveal that Santyl® collagenase induces post-debridement wound healing through the liberation of bioactive matrix-derived peptides within the wound bed, and that a "combinatorial" peptide created from some of the individual matrix domains fosters wound healing in vivo at a dose equivalent to that of Santyl®. Finally, as an extension of our studies of RhoGTPase in the regulation of pericyte chemo-mechanical control of angiogenesis, we show that key perturbations in the downstream pericyte RhoGTPase effectors, LIM-kinases and cofilin, promote endothelial cell cycle re-entry that may contribute to the development of vascular proliferative lesions in diabetic retinopathy. Overall, our findings should inform the development of next-generation molecular and cellular therapeutics capable of repairing difficult-to-heal wounds and abrogating or ameliorating pathologic neovascularization in diabetic retinopathy.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Cellular & Molecular Physiology.; Advisor: Ira Herman.; Committee: Brent Cochran, Guofu Hu, and Harold Dvorak.; Keywords: Medicine, Biology, and Surgery.